Knowledge, Attitudes, and Practices Regarding Chagas Disease in Micro-Territories of Fusagasugá–Cundinamarca, 2020–2022 - Bustos, Edison Huertas; Jaramillo , Hugo Fernando Ramírez; Gómez, Natalia Bocanegra; Salazar, Daniela Losada (Celebes Nursing Journal, 2026)
Introduction: Chagas disease remains a major neglected tropical disease (NTD) in Latin America, disproportionately affecting rural and socioeconomically vulnerable populations. Limited community knowledge and inadequate preventive practices contribute to persistent transmission. Objective: This study aimed to assess knowledge, attitudes, and practices (KAP) regarding Chagas disease among residents of selected rural micro-territories in Fusagasugá, Cundinamarca, between 2020 and 2022. Methods: A descriptive cross-sectional quantitative study was conducted among 166 adult residents from three rural micro-territories (Boquerón, El Triunfo, and Chinauta). Data were collected using a 27-item structured KAP questionnaire previously developed for endemic communities. Descriptive statistics were used to summarize frequencies and percentages. Results: Only 16.87% of respondents reported being familiar with Chagas disease, and 27.71% correctly identified the insect vector. Although 39.16% reported knowing how the disease is transmitted, knowledge regarding affected organs (9.04%) and vector ecology (31.33%) was limited. Despite these knowledge gaps, 77.11% expressed willingness to undergo diagnostic testing. Conclusion: The findings reveal significant deficiencies in community knowledge despite generally positive attitudes toward prevention. Strengthened community-based education strategies and nursing-led public health interventions are necessary to improve awareness and disease control in high-risk rural areas.